2020
DOI: 10.1096/fj.202002150r
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic responses from improved murine sepsis models can better mimic human surgical sepsis

Abstract: Historically, murine models of inflammation in biomedical research have been shown to minimally correlate with genomic expression patterns from blood leukocytes in humans. In 2019, our laboratory reported an improved surgical sepsis model of cecal ligation and puncture (CLP) that provides additional daily chronic stress (DCS), as well as adhering to the Minimum Quality Threshold in Pre-Clinical Sepsis Studies (MQTiPSS) guidelines. This model phenotypically recapitulates the persistent inflammation, immunosuppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Animal septic shock models have been largely used over the past decades to better understand pathophysiological mechanisms. Interestingly, several studies observed a similar modification of the gene expression profiles between the sepsis model and clinical samples, suggesting that animal models are relevant to evaluate the molecular mechanisms involved in the pathophysiology of sepsis [ 52 , 53 , 54 ], although this may be discussed as to their relevance to the clinic [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal septic shock models have been largely used over the past decades to better understand pathophysiological mechanisms. Interestingly, several studies observed a similar modification of the gene expression profiles between the sepsis model and clinical samples, suggesting that animal models are relevant to evaluate the molecular mechanisms involved in the pathophysiology of sepsis [ 52 , 53 , 54 ], although this may be discussed as to their relevance to the clinic [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…One murine sepsis model can be used to recapitulate infection and inflammatory responses with definite sepsis etiologies but cannot be extrapolated to all types of sepsis. Philip and his colleagues clearly proved that CLP þ DCS model mice can replicate surgical sepsis rather than community-acquired human sepsis in transcriptomic responses (28). CLP model mice do show PIICS characteristics and tend to recover (11,29).…”
Section: Discussionmentioning
confidence: 99%
“…DCS was conducted by placing mice in weighted plexiglass animal restraint holders (Kent Scientific; Torrington, CT) for 2 hours daily commencing the day after CLP. DCS was combined with CLP (CLP+DCS) to mimic the stress that occurs in patients when residing in an intensive care unit and better reflects human sepsis relative to CLP alone [34,35]. This model was previously used to describe age and sex-related changes in hippocampal transcription [15].…”
Section: Intra-abdominal Sepsis and Daily Chronic Stress Modelmentioning
confidence: 99%